Effect of Zinc (Zn) addition on Impact and Hardness Properties of Aluminium (Al) scrap - Ismail, Nur Faiqa; Zulkipli, Muhammad Asyraf; Yusof, Khairul Huda; Sundari, Ella; Putri, Eresyah (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
The aim of this study is to investigate the effect of zinc (Zn) material added to used aluminum (Al), which should affect its strength and hardness. In this current study, zinc material (Zn) was applied as an additional material to aluminum scrap, by mass percentages of Al 100% Zn 0%, Al 95% Zn 5%, Al 94.5% Zn 5.5%, and Al 94% Zn 6%, respectively. The results showed that the addition of zinc (Zn) had indeed affected the impact value and hardness properties of aluminum-zinc alloy (Al-Zn). The addition of zinc (Zn) at 6% yielded the highest effective strength value of 0.24 J/mm2, and the lowest effective strength value of 0.14 J/mm2. Although the highest hardness value was found by addition of 6% zinc (Zn), the average hardness was 73.76 HRB and the lowest hardness was 29.23 HRB. In conclusion, as the addition of Zinc (Zn) into the material composition increases, the impact and toughness properties of the material increases.